The rose garden : reading Marcel Proust - Gunnars, Kristjana (Red Deer, Alberta : Red Deer College Press, 1996)
Combining the genres of fiction, memoir, the familiar essay and theoretical speculation, The Rose Garden forms an unusual synthesis. The protagonist and narrator is a Canadian literary scholar on study leave in Germany. While there, her involvement with her books on the one hand and a love relationship on the other creates a surprising blend of life and fiction. Her readings in classical European texts forefront the question of a woman reader's response. Her involvement with her lover makes her wonder why there is so little difference between life and literature on the level of experience. This is an uncommon book that defies traditional rules of style and genre and provokes the question of what meaning literary works actually have in our lives.
Includes bibliographical references (pages 124-127).
Keywords: Farm life in art